Extract of Anadenanthera macrocarpa on Spodoptera frugiperda biology created with artificial diet - Moura, Jaqueline Zanon de; Pádua, Luis Evaldo de Moura; Silva, Paulo Roberto Ramalho e; Silva, Alcilane Arnaldo; Maggioni, Kellen (Comunicata Scientiae, 2012)
This research was conducted to evaluate the effect of leaf extract Angico-Preto (Anadenanthera macrocarpa ) on the biology of larvae of Spodoptera frugiperda. The larvae were reared on artificial diet, as Bowling, plus three different concentrations of extract. The following treatments were used: "T1" Diet without artificial extract Angico-Preto (control), "T2" artificial diet plus 2% of the extract Angico-Preto; "T3" artificial diet plus 4% of extract Angico-Preto, and "T4" artificial diet plus 6% of the extract Angico-Preto. To assess the biological S. frugiperda, was observed duration and viability of larval and pupal stages, and number of eggs per clutch every adult in the different treatments. Data were subjected to analysis of variance, followed by comparison of means using the Tukey test (P <0.05). It was found that the average duration of the larval stage (days) was lower in treatments whose diet was increased Angico-Preto Extract that differed significantly from the control (T1), with 28.22%. The viability of the larval phase (%) was also affected, treatment with the extract values were higher than T1 (65.0%), being higher in T4 (97.50%). The duration of the pupal stage (days) did not differ statistically different treatments. The viability of the pupal stage (%) was lower in T1 (47.71%) and highest in T4 (92.14%), and the number of eggs / mass was higher in treatments plus extract. We conclude that: the use extract Angico-Preto feeding S. frugiperda changed its biology; Different sources Angico-Preto on artificial diet can influence the duration and feasibility of the larval stage of S. frugiperda; Different sources Angico-Preto did not influence the duration, but may affect the viability of S. pupal frugiperda; Including extract Angico-Preto on artificial diet can influence the fecundity of S. frugiperda.